Presence and variability of culturable bioaerosols in three multi‐family apartment buildings with different ventilation systems in the Northeastern US. (30th September 2020) - Myers, Nirmala T.; Calderón, Leonardo; Pavilonis, Brian; Wang, Zuocheng; Xiong, Youyou; Sorensen‐Allacci, MaryAnn; Plotnik, Deborah; Senick, Jennifer; Gong, Jie; Krogmann, Uta; Andrews, Clinton J.; Mainelis, Gediminas
Abstract: Bioaerosol concentrations in residential buildings located in the Northeastern US have not been widely studied. Here, in 2011‐2015, we studied the presence and seasonal variability of culturable fungi and bacteria in three multi‐family apartment buildings and correlated the bioaerosol concentrations with building ventilation system types and environmental parameters. A total of 409 indoor and 86 outdoor samples were taken. Eighty‐five percent of investigated apartments had indoor‐outdoor (I/O) ratios of culturable fungi below 1, suggesting minimal indoor sources of fungi. In contrast, 56% of the apartments had I/O ratios for culturable bacteria above 1, indicating the prominence of indoor sources of bacteria. Culturable fungi I/O ratios in apartments serviced by central heating, ventilation, and air‐conditioning (HVAC) system were lower than those in apartments with window AC. The type of ventilation system did not have a significant effect on the presence of indoor culturable bacteria. A significant positive association was determined between indoor dew point (DP) levels and indoor culturable fungi ( P  < .001) and bacteria ( P  < .001), regardless of ventilation type. Also, residents in apartments with central HVAC did not experience extreme DP values. We conclude that building ventilation systems, seasonality, and indoor sources are major factors affecting indoor bioaerosol levels in residential buildings.